2018
DOI: 10.1080/09688080.2018.1535686
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health affecting utilisation of routine maternity services in Nepal: a narrative review of the evidence

Abstract: Nepal has one of the highest maternal and neonatal mortality rates among low-and middleincome countries. Nepal's health system focuses on life-saving interventions provided during the antenatal to postpartum period. However, the inequality in the uptake of maternity services is of major concern. This study aimed to synthesise evidence from the literature regarding the social determinants of health on the use of maternity services in Nepal. We conducted a structured narrative review of studies published from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 72 publications
(215 reference statements)
5
42
0
Order By: Relevance
“…Similarly, birth preparedness practice was found better among those with higher education than with lower education in Thailand, too [25]. Findings from a narrative review from Nepal advocated for the education linked with job opportunities in order to improve the health status of women [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, birth preparedness practice was found better among those with higher education than with lower education in Thailand, too [25]. Findings from a narrative review from Nepal advocated for the education linked with job opportunities in order to improve the health status of women [26].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reveals that the reason for home delivery is an easy and convenient environment which is also influenced by different sociodemographic characteristics [31]. A published review stated that higher socioeconomic status, education, privileged ethnicities, Hindu people, having access to transport and health services, getting family support, able to decide themselves, empowered, and having a birth preparedness plan are the major determinants of maternal health [26]. Another study concluded that emphasis should be given to women without education, to improve accessibility and provide advice on birth preparedness and danger signs to reduce home delivery [32].…”
Section: Characteristicsmentioning
confidence: 99%
“…A few HPs were performing assisted vaginal deliveries and manual removal of placenta, but PHCCs were not because of a lack of cases to perform these signal functions in the last three months in the PHCCs. The possible rationale for no cases in PHCCS might be due to shorter travel time or distance to the nearest referral/higher-level health facility (Khatri and Karkee 2018). The other reasons for unavailability of a case to perform signal functions may be the non-risk taking attitude of health workers.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of women with a postpartum check-up within 2 days after the delivery increased from 17% in 2001 to 57% in 2016. Khatri and Karkee (2018) found that limited means of transport, unequal access to health facilities, and lack of awareness, social exclusion, poor daily living conditions, and poor family support for care-seeking behaviour of health services are the core barriers to safe motherhood services.…”
Section: The Health Mosaic Of Adult Women Of Reproductive Years Status Of Safe Motherhood Carementioning
confidence: 99%